EXPERIMENTAL INVESTIGATION OF AMINE-BASED GRAPHENE NANOSUSPENSION FOR CO2 ABSORPTION - Nur Azni Farhana Mazri; A Arifutzzaman; Mohamed Kheireddine Aroua (Malaysian Journal of Science, 2024)
Absorption is the most widely used carbon dioxide (CO2) removal technology. The CO2 absorption performance of monoethanolamine (MEA), the most commonly used CO2 absorbent, can be improved by suspending nanoparticles. This work examined the performance of graphene nanoplatelets (GNPs) as additives to enhance CO2 absorption in MEA. The GNPs were characterized by HRTEM, FTIR, and XRD. The study examined the influence of GNP concentrations on CO2 absorption at room temperature. The images from HRTEM confirmed that the implemented graphene consists of several layers of graphene sheets. Increasing the loading of particles increased the solubility of CO2 until the optimum concentration was reached. From this work, it is evident that incorporating GNPs into MEA enhances the CO2 absorption performance of MEA. Thus, the addition of nanoparticles to the absorbent can enhance its CO2 absorptivity.